Exploring the Relationship between Play-Based Learning and Creativity Development in Preschoolers in Ibadan South- West Local Government - Adepeju , Oyegoke, Deborah; Iyabode, Abioye Jemimah Anuoluwapo; Olawale, Olatunji, Saheed; Adigun, Adejare, Sodiq (Journal of Innovation in Education and Social Research, 2024)
This study explored the relationship between play-based learning and creativity development in preschoolers in Ibadan South- West. The research aimed to understand how digital tools, physical activities, socio-economic and cultural factors, teachers' attitudes, and leadership influence the effectiveness of play-based learning. Six purposes and six research questions guided the study. A mixed-methods research design was employed, incorporating both quantitative and qualitative approaches. A sample of 200 preschool teachers, administrators, and parents was selected using a multistage sampling technique. Data were collected through structured questionnaires, interviews, and observation checklists. Pearson's correlation and regression analysis were used for quantitative data analysis, while thematic analysis was applied to the qualitative data. The results showed a significant positive relationship between play-based learning and creativity development, highlighting the influence of digital tools and physical activities. Challenges related to socio-economic constraints, leadership, and teacher capacity were also identified. The study recommends targeted teacher training, enhanced leadership support, and curriculum reforms to strengthen the integration of play-based learning in early childhood education.